Durability of an UHPC containing spent equilibrium catalyst - Matos, A. M. (2021)
UHPC is an advanced cementitious material able to meet the current construction industry challenges regarding structural safety and durability. However, new UHPC formulations with limited shrinkage are still being pursued to reduce residual tensile stresses in the UHPFRC layers, for rehabilitation/strengthening applications. This investigation estimates the durability of a non-proprietary UHPC incorporating a by-product originated by the oil refinery industry (ECat), as an internal curing agent. Direct and indirect transport properties measurements as well as the carbonation assessment and evaluation of dimensional resilience to potential deleterious reactionsrevealed that the new UHPC possesses an excellent durability performance, typical of these materials. These results combined with its self-compacting ability, low autogenous shrinkage and high compressive strength confirm the belief in the role of this new UHPC towards a high-tech construction.